The Effect of Restaurant Promotion on Consumer Intention to Buy in Jakarta - Raden Nana Kusdiana; Melly Arpila Suharun; Nurul Sukma Lestari (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
A consumer has the urge to buy a product, so that consumer already has an interest in buying a product. To attract consumers to buy, producers will communicate by promoting their products either online or offline. In this study, the method used by the author is a quantitative method. The type of research used is associative research, namely research that aims to determine the effect of one variable on another. This study aims to find out how promotion is at restaurants in Jakarta, to find out how much consumer buying interest is towards restaurants in Jakarta, to find out how much influence promotion has on consumer buying interest on buying interest at restaurants in Jakarta. This research was conducted in the city of Jakarta which took place in May 2022. The research population was taken from consumers in the city of Jakarta. The results of this study indicate that the research conducted and disseminated through questionnaires influence of promotion on consumer buying interest in Jakarta is positive, which means that promotion has an effect on consumer buying interest in Jakarta.